Anatomical approaches in locally advanced and recurrent pelvic malignancy. Issue 11 (November 2022) - Collins, Danielle; Jones, Ross; Griffiths, Ben
Abstract: Pelvic exenteration is a complex, technically challenging procedure requiring detailed anatomical knowledge. Understanding the complexity of the pelvis beyond TME is an essential requirement for both operative planning and execution. This paper highlights the key anatomical approaches to extended pelvic resection as relevant to the Colorectal Surgeon.